Robust Image Authentication in the Presence of Noise - Živić, Nataša (Springer International Publishing : Imprint: Springer, 2015)
This book addresses the problems that hinder image authentication in the presence of noise. It considers the advantages and disadvantages of existing algorithms for image authentication and shows new approaches and solutions for robust image authentication. The state of the art algorithms are compared and, furthermore, innovative approaches and algorithms are introduced. The introduced algorithms are applied to improve image authentication, watermarking and biometry.    Aside from presenting new directions and algorithms for robust image authentication in the presence of noise, as well as image correction, this book also:   Provides an overview of the state of the art algorithms for image authentication in the presence of noise and modifications, as well as a comparison of these algorithms, Presents novel algorithms for robust image authentication, whereby the image is tried to be corrected and authenticated, Examines different views for the solution of problems connected to image authentication in the presence of noise, Shows examples, how the new techniques can be applied to image authentication, watermarking and biometry. This book is written on the one hand for students, who want to learn about image processing, authentication, watermarking and biometry, and on the other hand for engineers and researchers, who work on aspects of robustness against modifications of secure images.